2021
DOI: 10.1016/j.gr.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Provenance and tectonic setting of the Paleozoic Tamatán Group, NE Mexico: Implications for the closure of the Rheic Ocean

Abstract: The Huizachal-Peregrina Anticlinorium in northeastern Mexico comprises a wide variety of Precambrian and Paleozoic basement units. In this work, Silurian-to-Permian unmetamorphosed siliciclastic successions (i.e., Cañón de Caballeros, Vicente Guerrero, Del Monte, and Guacamaya formations) forming the Tamatán Group is described; the group overlies the Novillo metamorphic complex, which is the northernmost exposed region of the Oaxaquia microcontinent. In this paper, a provenance model for the Tamatán Group is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 108 publications
(246 reference statements)
0
11
0
Order By: Relevance
“…420-410 Ma population observed in the Black Warrior basin. The Maya Mountains also expose Late Silurian plutons of compatible age (Steiner and Walker, 1996;Martens et al, 2010), and the Maya block has been interpreted to be located near bi-modal rift-drift, backarc, and arc tectonism (Casas-Peña et al, 2021) that is compatible with the variable Th/U values observed in Black Warrior strata. The Yucatan/Maya block has been proposed as a source of ca.…”
Section: Late Silurian-early Devonian Zircon Sourcementioning
confidence: 77%
“…420-410 Ma population observed in the Black Warrior basin. The Maya Mountains also expose Late Silurian plutons of compatible age (Steiner and Walker, 1996;Martens et al, 2010), and the Maya block has been interpreted to be located near bi-modal rift-drift, backarc, and arc tectonism (Casas-Peña et al, 2021) that is compatible with the variable Th/U values observed in Black Warrior strata. The Yucatan/Maya block has been proposed as a source of ca.…”
Section: Late Silurian-early Devonian Zircon Sourcementioning
confidence: 77%
“…2400 Ma and another at ca. 240 Ma (Casas‐Pena et al, 2021). Thus, all pre‐360 Ma grains in the Huizachal Group sandstone could have come from rocks that are exposed within 10 km of the studied outcrops near Ciudad Victoria and are known or presumed to underlie the outcrops near Aramberri and Galeana.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible local sources for this detritus. One is several units of the Tamatan Group: the 350–340 Ma Aserradero Rhyolite and the Guacamaya Formation, which yielded multiple detrital zircon grains with 206 Pb/ 238 U dates between 335 and 320 Ma (Casas‐Pena et al, 2021; Ramirez‐Fernandez et al, 2021). The second possibility is the East Mexico Arc and Anatectite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option is that these Ordovician to Devonian zircons come from the Carboniferous Santiago Formation from Oaxaca that contains two clusters, one of 480-450 Ma (peak at 471) and another of 365-335 Ma (peak at 358 Ma) (Gillis, Gehrels, Ruiz, & de Dios González, 2005). Recently, Casas-Peña et al (2021) report a peak at ~426 Ma in detrital zircon grains from sandstones from the Cañ on de Caballeros Fm. of the Tamatán Group of the Ciudad Victoria Block, which can also represent a source.…”
Section: Palaeozoic and Mesozoicmentioning
confidence: 99%